Cannabinoid overrides triggers of GABAergic plasticity in vestibular circuits and distorts the development of navigation - Wei Shi; Kenneth Lap-Kei Wu; Mengliu Yang; Francisco Paulo De Nogueira Botelho; Oscar Wing-Ho Chua; Hui-Jing Hu; Ka-Pak Ng; Ulysses Tsz-Fung Lam; Kin-Wai Tam; Chun-Wai Ma; Daisy Kwok-Yan Shum; Ying-Shing Chan (iScience)
Summary: Early life exposure to cannabis can result in long-lasting deficits in spatial navigation. We ask if the development of this behavior is subject to early life activity of type I cannabinoid receptor (CB1R) in the vestibular nucleus. In rodents, we found that local exposure to CB1R agonist within the first postnatal week, but not thereafter, led to a decline in the induction efficacy of long-term depression at GABAergic synapses (LTDGABA), a key step in the hard-wiring of vestibular circuits. Within this critical period, endocannabinoid-mediated LTDGABA at inhibitory neurons was selectively triggered by cholecystokinin, whereas that at excitatory neurons was by serotonin. Neonatal exposure to cannabinoids extended the phase of high GABAergic synaptic plasticity and overrode the synapse-specific, modulatory mechanism for plasticity. Such treatment delayed the postnatal emergence of vestibular-dependent reflexes and deranged adult navigational behavior. Deficits in higher functions are thus attributable to the maldevelopment of sensory processing circuits resulting from early cannabis exposure.